2022
DOI: 10.1007/s10792-022-02525-w
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on the prevalence of computer vision syndrome among medical students in Riyadh, Saudi Arabia

Abstract: Purpose To estimate the prevalence of computer vision syndrome (CVS) among university medical students in Riyadh, Saudi Arabia, after establishing remote learning during COVID-19 pandemic and to compare settings of electronic device usage and patterns of CVS protective measures applied by students before and during this pandemic. Methods This is an observational descriptive cross-sectional study which included 1st to 5th year medical students who were actively enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…These findings are in line with the study done by Almousa et al who reported that the least symptoms were double vision (18.3%) and watery eyes (35.7%). 23 Additionally, in a study conducted by Gammoh in Jorden, double vision (18.3%) and heavy eyelids (28.7%) were the least symptoms. 24 Double vision (1%) and difficulty in refocusing the eye (8%) were the least symptoms reported by Iqball.…”
Section: Resultsmentioning
confidence: 97%
“…These findings are in line with the study done by Almousa et al who reported that the least symptoms were double vision (18.3%) and watery eyes (35.7%). 23 Additionally, in a study conducted by Gammoh in Jorden, double vision (18.3%) and heavy eyelids (28.7%) were the least symptoms. 24 Double vision (1%) and difficulty in refocusing the eye (8%) were the least symptoms reported by Iqball.…”
Section: Resultsmentioning
confidence: 97%
“…The pooled prevalence of computer vision syndrome was 74% (95% CI: 66, 81) (10,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The study with the lowest proportion was conducted in Saudi Arabia, with a prevalence of 35% (95% CI: 31, 40) (20), while the highest was conducted in Pakistan, with a prevalence of 99% (95% CI: 97, 100) (17).…”
Section: Pooled Prevalence Of Computer Vision Syndromementioning
confidence: 99%
“…Eighteen cross-sectional studies examining the prevalence of computer vision syndrome during the COVID-19 pandemic, published between 2021 and 2022, were included (10, 14-30) (Table 2). The total sample included 10337 participants from 12 countries (n = 18) (10, 14-30): India (n = 3) (14, 21, 28), Saudi Arabia (n = 3) (15,20,29), Ethiopia (n = 1) (16), Pakistan (n = 1) (17), China (n = 2) (18, 26), Egypt (n = 1) (19), Paraguay (n = 1) (22), Peru (n = 1) (23), South Africa (n = 1) (24), Bangladesh (n = 1) (25), Thailand (n = 2) (10, 27), and Turkey (n = 1) (30). The sample size varied from 74 in a study of Chinese medical students at the University of Sichuan (18) to 2476 in a survey of high school students in Thailand (10).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…donde menciona que, los errores de refracción no son factores de riesgo para tener más de tres síntomas del SVI. 10 Por el contrario, otro estudio, difiere con nosotros al mencionar que, si la visión binocular y los errores refractarios no son modificados para mejora, puede predisponer al desarrollo del SVI; lo cual se puede deber a la descompensación del esfuerzo visual. 9,17 Frente a la presencia de enfermedades sistémicas puede predisponer la aparición de errores refractarios y acelerar la aparición de síntomas que conducen al síndrome visual informático, por lo que, el paciente debe entender que su visión sufrirá cambios con el tiempo y deberá acudir a evaluaciones oculares rutinarias.…”
Section: Discussionunclassified
“…Otra investigación adiciona síntomas musculoesqueléticos como el dolor de cuello, hombro y espalda presente en el 84,3%, dolor de cabeza (71,1%) y ojos secos (68%). 10 Por otro lado, se encontró un estudio conformado en su mayoría por hombres (60%) donde sólo el 20% de tuvieron múltiples síntomas oculares los cuales fueron el dolor ocular (9%), sequedad ocular (8%), el lagrimeo en los ojos y enrojecimiento de los ojos (6%). 18 Esto reforzaría nuestra teoría, relacionando al sexo femenino con la aparición de síntomas múltiples y por ende el desarrollo del SVI.…”
Section: Discussionunclassified